2010
DOI: 10.1186/1476-511x-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids synergize with lipid droplet binding thalidomide analogs to induce oxidative stress in cancer cells

Abstract: BackgroundCytoplasmic lipid-droplets are common inclusions of eukaryotic cells. Lipid-droplet binding thalidomide analogs (2,6-dialkylphenyl-4/5-amino-substituted-5,6,7-trifluorophthalimides) with potent anticancer activities were synthesized.ResultsCytotoxicity was detected in different cell lines including melanoma, leukemia, hepatocellular carcinoma, glioblastoma at micromolar concentrations. The synthesized analogs are non-toxic to adult animals up to 1 g/kg but are teratogenic to zebrafish embryos at micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 39 publications
2
57
0
3
Order By: Relevance
“…In the same vein, Puskas et al (2010) demonstrated that EPA and DHA but not monounsaturated oleic acid synergised effectively with lipid-binding thalidomide analogues to induce oxidative stress in cancer cells. Albeit that such strategies aim to expose cancer cells to lethal antitumorigenic consequences, they also underline the capacity of PUFAs to exert dramatically different influences in accordance with the extent to which they are either protected from or are a focus for oxidative damage.…”
Section: Discussionmentioning
confidence: 86%
“…In the same vein, Puskas et al (2010) demonstrated that EPA and DHA but not monounsaturated oleic acid synergised effectively with lipid-binding thalidomide analogues to induce oxidative stress in cancer cells. Albeit that such strategies aim to expose cancer cells to lethal antitumorigenic consequences, they also underline the capacity of PUFAs to exert dramatically different influences in accordance with the extent to which they are either protected from or are a focus for oxidative damage.…”
Section: Discussionmentioning
confidence: 86%
“…In our earlier study, we have discovered in-house synthesized thalidomide analogs localizing to lipid droplets on human cancer cells (Puskás et al, 2010). Being blue fluorescent and plasma membrane permeable, these dyes are attractive candidates as fluorescent reporters for Lipid droplet (LD) studies in plant cells.…”
Section: Localization and Toxicity Of Ac Chemicals On Plant Suspensiomentioning
confidence: 99%
“…Moreover, biocompatibility and toxicity of these chemicals may also be different for plant cells. In addition to Ac-202 and Ac-1041 chemicals (Puskás et al, 2010), we have also included Ac-201 (a positional isomer of Ac-202) to test suitability of these chemicals as LD probes in plant cells. Using confocal laser scanning microscopy and fine rice suspension cultures (Oryza sativa L. japonica cv.…”
Section: Localization and Toxicity Of Ac Chemicals On Plant Suspensiomentioning
confidence: 99%
See 1 more Smart Citation
“…A lipid cseppecskék az endoplazmatikus retikulumban alakulnak ki. Az azokhoz kötődő kismolekulák pedig képesek befolyásolni illetve megváltoztatni a lipid cseppecskékhez köthető homeosztázist és az endoplazmatikus retikulum stresszen keresztül beindítani az apoptózist [82].…”
Section: Ac-915 Talidomid Analóg Toxikogenomikai Vizsgálataunclassified